Trust framework for self-sovereign identity in metaverse healthcare applications - Alan Ling; Sergey Butakov (Data Science and Management)
The research community and digital sector are currently engaged in the development of diverse services within the metaverse ecosystems. Conversely, as concerns about safeguarding personal privacy mount, individuals anticipate exercising greater authority over the way third parties make use of sensitive information, such as medical data. This study aims to develop tools that can facilitate the provision of healthcare services within the metaverse ecosystem in a safe and trustworthy way. This project proposes a trust framework for digital healthcare applications to run in a metaverse environment. The framework is based on the use of self-sovereign identity (SSI) and has been tested on the design principles outlined for the SSI-based architecture. This study outlines two use-case scenarios that can serve as foundations for implementing a trust framework.